RANCANG BANGUN SISTEM INFORMASI PERKEMBANGAN AKADEMIK PADA PENDIDIKAN ANAK USIA DINI (PAUD) BERBASIS WEB PADA SATUAN PAUD SEJENIS (SPS) AL-FAUZAN: Kehadiran teknologi komputer saat ini kian berkembang cepat, pesat dan kompleks menjadikan kebutuhan akan informasi manusia meningkat, terutama dalam pendidikan sehingga bidang pendidikan harus dapat mengikuti perkembangan teknologi terutama teknologi komputer. Dalam bidang pendidikan, sistem informasi perkembangan akademik pada anak usia dini menjadi - Aliffiyah Hanifah; Muhammad Feizal (CV. Multi Kreasi Media, 2022)
The presence of computer technology is currently growing rapidly, rapidly and complexly, making the need for human information increase, especially in education so that the education sector must be able to keep up with technological developments, especially computer technology. In the field of education, an information system on academic development in early childhood is a major need for relevant managers to assist the process of managing children's academic development data so as to produce useful and accurate information. Based on the results of interviews, SPS Al-Fauzan currently does not have an academic development information system, and is unable to record, process, search, store and present data on children's educational development and reports (transcripts) of children's learning development results which are still done manually. This study aims to create an academic development information system in Early Childhood Education (PAUD) that can facilitate operators, teachers and parents in inputting administrative data and reports (transcripts) of children's learning development results. In designing this system using a waterfall and web-based model that can shorten the process and time required by using PHP as a programming language and Mysql as a database and using the CodeIgniter Framework. This system can provide information such as school year data, academic activities, teachers, students, classes and announcements. In addition, the resulting data can be more accurate and can avoid errors.